The Effect of Service Quality and Passenger Fares on Consumer Decisions Using DAMRI Buses - Astuti, Dina; Heryati, Yati; Hajjad, Mu’fidatul Nurul (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to assess the impact of service quality and passenger fares on consumer decisions regarding the use of the Mamuju Branch Damri Bus. Specifically, the research has two primary objectives: first, to determine the individual influences of service quality and passenger fares on consumer decisions; and second, to explore the combined effect of both factors on these decisions. Employing a quantitative research approach, the study utilizes two independent variables (service quality and passenger fares) and one dependent variable (consumer decision to use the Mamuju Branch Damri Bus). The methodology includes the application of multiple statistical tests to ensure the validity and reliability of the data collected. These tests include a validity test to ascertain the appropriateness of the research instruments, a reliability test to ensure consistent results, and multiple linear regression to analyze the impact of independent variables on the dependent variable. Additionally, t-tests (partial) and F-tests (simultaneous) are conducted to examine the significance of the effects. A sample of 96 respondents was selected for this study, and data were processed using SPSS software version 24.0. This facilitated a detailed analysis of how service quality and passenger fares influence consumer decisions, both individually and collectively. The findings revealed that both service quality and passenger fares significantly affect consumer decisions to use the Damri Bus at the Mamuju Branch, individually and in combination. This underscores the importance of these factors in shaping consumer behaviors and preferences in the context of public transportation.